Customer-Centered Design: A New Approach to Web Usability - Chandler, Kreta; Hyatt, Karen (Pearson, 2002)
"This book provides readers what they need to know to greatly enhance website usability and the customer online shopping experience" -Jakob Nielsen, author of best-selling title, Designing Web Usability To succeed on the web, companies must understand their customers' needs and goals more thoroughly than ever before-and use that information to build sites that deliver an outstanding shopping experience. Customer-Centered Design offers a systematic blueprint for doing just that. Leading marketing experts and usability professionals Kreta Chandler and Karen Hyatt bring together state-of-the-art techniques that address your goals for short- and long-term profitability and your customers' demands for convenience, simplicity, and satisfaction. This book reveals: What you must know about your customers-and how to get and use that information more efficiently Five views of the online store: as software system, catalog, communications vehicle, sales rep, and retail shopping experience Measuring your customers' experience with your site to stay on the leading edge Blending successful techniques from catalogs, retail and e-tail stores to create a new shopping environment Facilitating sales by helping your customers make buying decisions Understand how the products you sell influence your site's information architecture and design.